(untitled) (Experimental biology, 2021)
The aim of the work was to evaluate the effectiveness of combined therapy of the extract of polyphenols isolated from the roots of Limonium Gmelinii and mesenchymal stem cells (MSCs) under conditions of experimentally induced ischemic brain damage in vivo. The object of this study were outbred male Wistar rats weighing 280-300 g. To create a model of focal ischemic stroke, occlusion of the middle cerebral artery (MCAO) was performed. Animals of the experimental groups received Kermek of Gmelin intragastrically; MSC transplantation was carried out by injection through the common femoral vein. Intravital assessment of the survival and distribution of transplanted MSCs was carried out using a micro CT IVIS Spectrum apparatus. Analysis of the sensorimotor functions of animals was performed using the test " Beam walk." The results of the study showed that transplanted MSCs are localized in the brain only in animals with MCAO, however, their localization in the thoracic and abdominal region was noted both in animals with and without stroke. Evaluation of sensorimotor activity showed that in animals that received MSC transplantation, partial restoration of motor functions occurred, and with combined therapy with Limonium Gmelinii extract and MSC on day 14, the motor activity of rats was restored almost to the control values. Thus, combined therapy with Limonium Gmelinii extract and mesenchymal stem cells is a more effective approach as compared to MSC monotherapy. Key words: ischemic stroke, Limonium Gmelinii, plant polyphenols, mesenchymal stem cells.